Variation among cleft centres in the use of secondary surgery for children with cleft palate: a retrospective cohort study. Issue 1 (31st August 2017) - Sitzman, Thomas J; Hossain, Monir; Carle, Adam C; Heaton, Pamela C; Britto, Maria T
Abstract : Objectives: To test whether cleft centres vary in their use of secondary cleft palate surgery, also known as revision palate surgery, and if so to identify modifiable hospital factors and surgeon factors that are associated with use of secondary surgery. Design: Retrospective cohort study. Setting: Forty-three paediatric hospitals across the USA. Patients: Children with cleft lip and palate who underwent primary cleft palate repair from 1999 to 2013. Main outcome measures: Time from primary cleft palate repair to secondary palate surgery. Results: We identified 4939 children who underwent primary cleft palate repair. At 10 years after primary palate repair, 44% of children had undergone secondary palate surgery. Significant variation existed among hospitals (p<0.001); the proportion of children undergoing secondary surgery by 10 years ranged from 9% to 77% across hospitals. After adjusting for patient demographics, primary palate repair before 9 months of age was associated with an increased hazard of secondary palate surgery (initial HR 6.74, 95% CI 5.30 to 8.73). Postoperative antibiotics, surgeon procedure volume and hospital procedure volume were not associated with time to secondary surgery (p>0.05). Of the outcome variation attributable to hospitals and surgeons, between-hospital differences accounted for 59% (p<0.001), while between-surgeon differences accounted for 41% (p<0.001). Conclusions: Substantial variation in the hazard of secondary palate surgery exists depending on a child's age at primary palate repair and the hospital and surgeon performing their repair. Performing primary palate repair before 9 months of age substantially increases the hazard of secondary surgery. Further research is needed to identify other factors contributing to variation in palate surgery outcomes among hospitals and surgeons.